Resolution Adopted by the Special Political Committee at its 376th meeting. Seventeenth Session. Agenda Item 85. A/SPC/77 - Héderváry, Claire de (1962)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly This draft reaffirms the objectives of the previous resolutions; requests that the Secretary General take any initiatives he deems helpful in relation to the Hungarian question; expresses appreciation to the Special Representative on Hungary Sir Leslie Munro for his efforts regarding implementations of the previous resolutions.